Burning Fog: Cognitive Impairment in Burning Mouth Syndrome - Canfora, Federica; Calabria, Elena; Cuocolo, Renato; Ugga, Lorenzo; Buono, Giuseppe; Marenzi, Gaetano; Gasparro, Roberta; Pecoraro, Giuseppe; Aria, Massimo; D'Aniello, Luca; Mignogna, Michele Davide; Adamo, Daniela (Frontiers in Aging Neuroscience, 2021)
Background: Cognitive impairment (CI) is commonly associated with chronic pain experience, but it has never been evaluated in patients with Burning Mouth Syndrome (BMS). The purpose of this study was to assess the prevalence of CI in these patients and evaluate its relationships with potential predictors such as pain, mood disorders, blood biomarkers and white matter changes (WMC). Methods: A case-control study was conducted by including 40 BMS patients and an equal number of healthy controls matched for age, sex and education. Neurocognitive assessment [Mini Mental Status Examination (MMSE); Digit Cancellation test (DCT); Digit Span Forward and Backwards (FDS and BDS); Corsi Block-tapping test (CB-TT); Rey Auditory Verbal learning Test (RAVLT); Copying Geometric Drawings (CGD); Frontal Assessment Battery (FAB) and Trail Making A and B (TMT-A and TMT-B)]; psychological assessment [Hamilton rating scale for Depression and Anxiety (HAM-D and HAM-A); Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS), Short Form (36) Healthy Survey (SF-36)] and pain assessment [Visual Analogic Scale (VAS) and Total score of Pain Rating index (T-PRI) , Brief Pain Inventory (BPI) and Pain Detect questionnaire (PD-Q)] were performed. In addition, blood biomarkers and Magnetic Resonance Imaging (MRI) of the brain for detection of Age-Related White Matter Changes (ARWMC) were recorded. Descriptive statistics, including the Mann-Whitney U test and Spearman’s correlation analysis were used. Results: Patient with BMS had impairments in most of cognitive domains compared with controls (p < 0.001**) except in RAVLT and CGD. The HAM-D, HAM-A, PSQI, ESS, SF-36, VAS, T-PRI, BPI and PD-Q scores were statistically different between BMS patients and controls (p <0 .001**). The WMC frequency and ARWMC scores in the right and left temporal lobes were higher in the BMS patients (p:0.023*). Conclusions: BMS is associated with a higher cognitive decline, particularly in attention, working memory, executive function while the praxis constructive skills and verbal memory are preserved. The early identification of CI and associated factors may help clinicians to identify patients at risk to develop through time neurodegenerative disorders, such as Alzheimer’s disease and vascular dementia, in order to plan an early comprehensive and multidisciplinary assessment and treatment.